2022
DOI: 10.3390/su142416789
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Analysis Method of Heavy Metals in Organic Fertilizers: A Review

Abstract: Heavy metals in organic fertilizers pose a risk to the agricultural ecosystem. The environmental risk of heavy metals depends not only on the total amount but also on the speciation. Hence, more information on heavy metals speciation in organic fertilizers is needed to avoid adverse effect. At present, the speciation information of heavy metals is usually obtained by the single-extraction method and sequential extraction method. Common heavy metals that have received attention include Cu, Zn, Pb, Cd, Cr, Hg an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The content of nickel reduced in all fractions after the experiments finished (plant collection). The mobility of heavy metals resulting in uptake by plants is dependent on the content of organic matter (fraction 4 in Tessier sequential extraction) [23,24]. The stability of humic substance-metal cation complexes depends on the pH of the medium and increases with pH, the nature of the ions and the presence of different ions.…”
Section: Resultsmentioning
confidence: 99%
“…The content of nickel reduced in all fractions after the experiments finished (plant collection). The mobility of heavy metals resulting in uptake by plants is dependent on the content of organic matter (fraction 4 in Tessier sequential extraction) [23,24]. The stability of humic substance-metal cation complexes depends on the pH of the medium and increases with pH, the nature of the ions and the presence of different ions.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a 62-year experiment, Mensik et al [17] showed that fertilisation with only NPK reduces the content and quality of OM (lower content of TOC, humic substances, predominance of FAs over HAs), whereas the use of manure resulted in an increase in the content and quality of OM (increase in TOC, humic substances and humic acids). In addition to the undoubted benefits of such fertilisation, there is a danger of enriching soils with heavy metals contained in these fertilisers [18,19]. Consumption of food produced on soils with organic fertilisers containing heavy metals in their composition can cause serious health problems for both animals and humans [20].…”
Section: Introductionmentioning
confidence: 99%
“…The reducible state and oxidizable state can be transformed into acid extractable state under certain conditions, which can be indirectly absorbed and utilized by plants. Residual heavy metals are mainly found in the soil lattice, with high stability, which are not easily released in a short time and cannot be absorbed and utilized by plants (Wang et al, 2005(Wang et al, , 2022. Bian et al (2014) found that biochar addition considerably reduced Pb bioavailability by 59.1%.…”
Section: Introductionmentioning
confidence: 99%